2016
DOI: 10.1038/srep31961
|View full text |Cite
|
Sign up to set email alerts
|

Empathy promotes altruistic behavior in economic interactions

Abstract: What are the determinants of altruism? While economists assume that altruism is mainly driven by fairness norms, social psychologists consider empathy to be a key motivator for altruistic behavior. To unite these two theories, we conducted an experiment in which we compared behavior in a standard economic game that assesses altruism (the so-called Dictator Game) with a Dictator Game in which participants’ behavioral choices were preceded either by an empathy induction or by a control condition without empathy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
82
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 113 publications
(102 citation statements)
references
References 24 publications
(38 reference statements)
10
82
1
Order By: Relevance
“…The findings of this study provide partial support for the hypothesis, as it was found that participants induced with empathic feelings spent more time to donate grains of rice to charity than participants not induced with emotions at all. Therefore, this finding supports previous research (e.g., Farrelly et al, ; Klimecki et al, ) that empathic feelings can lead to altruistic behaviour by revealing that such effects are present in interactions with real world charities where time spent is the donation requested. Furthermore, by using time as the currency, we show that inducing empathy can lead to longer lasting prosocial behaviour to alleviate negative mood that is similar to the instantaneous effects of donating money that previous studies have found (e.g., Klimecki et al, ).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The findings of this study provide partial support for the hypothesis, as it was found that participants induced with empathic feelings spent more time to donate grains of rice to charity than participants not induced with emotions at all. Therefore, this finding supports previous research (e.g., Farrelly et al, ; Klimecki et al, ) that empathic feelings can lead to altruistic behaviour by revealing that such effects are present in interactions with real world charities where time spent is the donation requested. Furthermore, by using time as the currency, we show that inducing empathy can lead to longer lasting prosocial behaviour to alleviate negative mood that is similar to the instantaneous effects of donating money that previous studies have found (e.g., Klimecki et al, ).…”
Section: Discussionsupporting
confidence: 91%
“…Therefore, this finding supports previous research (e.g., Farrelly et al, 2015;Klimecki et al, 2016) that empathic feelings can lead to altruistic behaviour by revealing that such effects are present in interactions with real world charities where time spent is the donation requested. Furthermore, by using time as the currency, we show that inducing empathy can lead to longer lasting prosocial behaviour to alleviate negative mood that is similar to the instantaneous effects of donating money that previous studies have found (e.g., Klimecki et al, 2016). Interestingly, however, this effect of induced empathy did not lead to greater charitable donations as predicted than when another emotion, anger, was induced.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Several studies have verified the role of empathy and ToM for prosociality (Masten, Morelli, and Eisenberger 2011;Klimecki et al 2016;Hare et al 2010). Specifically, costly helping of others in need is predicted by both activation in the anterior insula and the temporoparietal junction (Tusche et al 2016).…”
Section: Consequences For Social Behaviourmentioning
confidence: 99%
“…Rather than evaluating hypotheses at the group level, the hypotheses are evaluated for each person separately. In social psychology, for example, it is often hoped or thought that if a hypothesis holds at the group level, this also applies to all individuals (see for example, Moreland & Zajonc, 1982;Klimecki, Mayer, Jusyte, Scheeff, & Schönenberg, 2016). Hamaker (2012) describes the importance of individual analyses using an example: Cross-sectionally, the number of words typed per minute and the percentage of typos might be negatively correlated.…”
Section: Introductionmentioning
confidence: 99%